Exploring family dynamics in Mitch Albom’s For One More Day through the lens of Bowen’s family systems theory - Tan, Noalester Karlson; Amran, Nurul Atiqah (Secholian Publication, 2024)
This study represents the culmination of a final-year project in literary criticism, integrating selected literary text with a theoretical framework, with roots tracing back to the 1940s and 1950s. The paper delves into exploring family dynamics and human behaviours in Mitch Albom’s For One More Day (2006). Through the lens of Bowen’s family systems theory (BFST), we utilize three concepts and aim to illuminate the intricate interplay of relationships within the family unit, encompassing the roles of the father, mother, and the protagonist himself. We proceed to investigate the transmission of emotional issues from the parents to the child, which culminates in Chick’s adoption of emotional cutoff as a coping mechanism. This study contributes to the understanding that people’s thoughts, emotions, and actions are shaped by the complex relationships rooted in their family of origin. The unresolved emotional issues within the family unit can jeopardise other new relationships. BFST sheds light on this dynamic relationship, making us understand that it is not just about identifying the cause of the problems but more about resolving the problems and finding solace through a proper closure to the unresolved trauma within the familial context.